Pengembangan booklet Berbasis Potensi Lokal Berdasarkan Inventarisasi Jenis Ikan di Wilayah Sungai Sedulun Sebagai Sumber Belajar Pada Materi Vertebrata Kelas Pisces - Yunita Yunita; Fitri Wijarini; Nursia Nursia (Biopedagogia, 2022)
This reserch aimed to produce a learning resource in the form of a quality local potential-based booklet referring to the inventory of fish species in River Sedulun area as a learning resource related to vertebrate materials on Pisces class assessed by several experts. The research was classified into RD (Research and Development) with a 4-D development model consisting of four stages: Defining, Designing, Developing, and Dissminating. However, this development was performed only until the 3rd stage (Development). The product feasibility tests were validated by the experts, including media expert, material expert, and practitioner. Meanwhile, the studentsâ€™ response data were obtained from the studentsâ€™ responses were respectively 82% (greatly feasible), 94% (greatly feasible), 84% (greatly feasible), and 91% (highly interested). Based on the research results, it can be concluded that the developed local potential-based booklet referring to the inventory ot fish species in River Sedulun area as a learning resource related to vertebrate materials on pisces class has met the criteria of highly feasible to be used as a learning resource for biology learning at school. Keywords: Learning Resource, Booklet, Vertebrate on Pisces ClassÂ